2021
DOI: 10.36681/tused.2021.60
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive argument-driven ınquiry in teaching antimicrobial resistance: Effects on students’ conceptual understanding and argumentation skills

Abstract: Developing and communicating evidence-based explanations are regarded asessential skills in 21st-centurylearning. These skills are central to the process of scientific argumentation. Hence, teachers must adhere toa student-centered pedagogy that cultivates students’ understanding and argumentation skills. Thisstudy investigated the effects of the Metacognitive Argument-Driven Inquiry (MADI) approach in promoting students’ conceptual understanding of AntimicrobialResistance and scientific argumentation skills. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The results of their study showed that the flipped inquiry-based approach did not make students perform better than the non-flipped inquiry-based learning environment in terms of the development of process skills and understanding. Although a flipped learning environment caters students' flexible learning, in-class sessions can provide better social interactivity and learning activities for students (Abate, 2004;Antonio & Prudente, 2021). However, the results for the effectiveness of blended instructional approach on students' attitudes and process skills are inconclusive considering the limited number of studies on these variables included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of their study showed that the flipped inquiry-based approach did not make students perform better than the non-flipped inquiry-based learning environment in terms of the development of process skills and understanding. Although a flipped learning environment caters students' flexible learning, in-class sessions can provide better social interactivity and learning activities for students (Abate, 2004;Antonio & Prudente, 2021). However, the results for the effectiveness of blended instructional approach on students' attitudes and process skills are inconclusive considering the limited number of studies on these variables included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These skills are at the core of the scientific argumentation process. Therefore, lecturers must adopt a student-centered pedagogy that fosters understanding and argumentation skills [25]. Knowledge is not information but a series of activities i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The final data on students' argumentation skills showed a significant increase, where almost all of the students' arguments were in the level 3 category, meaning that students were able to make claims accompanied by complete supporting grounds (data, justification and support). The increasing knowledge of students after learning concepts can lead to an increase in the number of students who can include data and make justifications in arguing (Antonio, RP., & Prudente, M.S., 2021). According to Putri (2018), learning with the PBL model can increase students' knowledge to improve student's ability to argue.…”
Section: Strength Of Student's Scientific Argumentmentioning
confidence: 99%